Digestibility of a Sorghum Blend with an Enzyme Complex in Diets for Pigs - Farfán-López, Charly; Colina, Janeth; Araque, Humberto; Mora, Franklin; De Basilio, Vasco (Agrociencia Uruguay, 2016)
An experiment in two periods of eight days each was conducted to determine the apparent total tract digestibility of dry matter (DDM), energy (ADE), and nitrogen (DAN) from a sorghum blend (SB) with an enzyme complex (EC) in diets for growing pigs.Twenty four pigs (35 kg live weight) distributed in a randomized block design (period as block) with four diets and six pigs per diet were used in a 2 × 2 factorial arrangement of treatments. The factors were two ingredients (SB and corn) with or without EC resulting in the following diets: basal with corn (BDC); BDC with the addition of EC (BDC+EC); SB-based diet (SBD) and SBD+CE. The pigs were individually allocated in metabolic cages for total collection of feces. Data were analyzed using PROC MIXED of SAS statistical software, using ANOVA tests, and the GLM-Tukey procedure. There was no effect of EC on the evaluated variables. The ADE varied significantly (P = 0.003) between the two ingredients with values of 3641.49 ± 42.95 kcal /kg DM and 3540.61 ± 55.82 kcal/kg DM for BDC and SBD, respectively. The DAN was greater (P = 0.002) in the BDC (81.75 ± 1.55%) than SBD (77.06 ± 3.44%). It is concluded that the addition of the EC had no effect on the DDM, DAN and ADE in the blend of sorghum grains evaluated in diets for growing pigs.